PELATIHAN TARI KREASI SEBAGAI PENINGKATAN KOMPETENSI GURU MI/PAUD/RA RADEN FATAH - Emy Yunita Rahma Pratiwi; Ratih Asmarani; Evita Widiyati; Muhammad Nuruddin; Claudya Zahrani Susilo (ABIDUMASY, 2020)
Abstract: This community service is one of the education services to the community, which is one of the programs in the field of KKNT of UNHASY Tebuireng Jombang students in Kedungbogo Village, Ngusikan District, Jombang Regency. One of those is conducting a dance training at Raden Fatah. The results of the study were: there is a lack of understanding of the concept and the importance of cultural arts education in classroom learning in terms of students’ character development into humanistic characters through creativity, sense, and intention. The method used in implementing this community service is as follows: a) partner Situation Analysis, b) literature study, c) preparation of material to be presented as a problem solution, d) testing the results, e) revision products, f) the training implementation, and g) Regular mentoring.Based on those problems, it can be concluded that a) there must be an improvement in skills and competence of teachers related to the teaching and learning process in the schools environments, b) this training (community service) is expected to make teachers understand the concept and the importance of cultural arts education c) there must be a development of students’ character to become humanistic character through creativity, taste, and initiative, displaying an attitude of appreciation for cultural arts, displaying creativity through cultural arts, and increase the participation of cultural arts events at the local, regional and global levels. Keywords: Dance, Competency, Professional, Teacher, Raden Fatah Abstrak: Pengabdian ini merupakan salah satu pengabdian perguruan tinggi kepada masyarakat, yaitu salah satu program di bidang pendidikan KKNT mahasiswa UNHASY Tebuireng Jombang di Desa Kedungbogo Kecamatan Ngusikan Kabupaten Jombang, diantaranya melaksanakan Pelatihan Tari di Raden Fatah. Hasil analisis yang ditemukan adalah: Kurang adanya pemahaman konsep dan pentingnya pendidikan seni budaya pada pembelajaran di kelas sehingga kurang dalam hal pengembangan karakter peserta didik menjadi manusia yang humanistis melalui olah cipta, rasa, dan karsa. Metode pelaksanaan PKM adalah sebagai berikut: a) Analisis Situasi Mitra, b) Pengkajian pustaka c) Penyusunan materi sebagai solusi masalah, d) Uji coba, e) Revisi produk, f) Pelaksanaan pelatihan, dan g) Pendampingan berkala. Berdasarkan permasalahan tersebut maka dapat disimpulkan bahwa perlu adanya a) peningkatan keterampilan maupun kompetensi guru yang berkaitan dengan proses belajar mengajar di lingkungan Sekolah Dasar/Madrasah Ibtidaiyah maupun PAUD/RA perlu ditingkatkan. b) adanya pelatihan dalam PKM ini diharapkan menjadikan guru memahami konsep dan pentingnya pendidikan seni budaya c) mengembangkan karakter peserta didik menjadi manusia yang humanistis melalui olah cipta, rasa, dan karsa, menampilkan sikap apresiasi terhadap seni budaya, menampilkan kreativitas melalui seni budaya, dan meningkatkan peran serta seni budaya pada tingkat lokal, regional dan global. Kata Kunci: Tari, Kompetensi, Professional, Guru, Raden Fatah